Exposure to particles in Portuguese swine production - Viegas, Susana (2013)
Several studies have shown that human exposures to airbome dust and microorganisms, such as bacteria and fungi, can cause respiratory diseases. Agricultural workers have been found to be at high risk of exposures to airborne particles. From a human health perspective dust exposure in pig farming is the most important risk because of the large number of workers needed in pig production and the increasing number of working hours inside enclosed buildings. In the pig buildings, particulate matters like dust play a role in not only deteriorating indoor air quality but also can cause an adverse health effect on workers. Generally, dust is recognized to adsorb and transport odorous compounds and biological agents. The aim of this study was to determine particles contamination in 7 swine farms located in Lisbon district, Portugal.